A Review of Electrokinetic Studies of Metal Sulphides - T. W. Healy; M. S. Moignard (Society for Mining, Metallurgy & Exploration, 1976)
The use of electrokinetic or zeta-potential phenomena in studies of the properties of mineral sulphides has increased greatly over recent years. This review aims to examine and discuss the body of literature on the subject of electrokinetic properties of sulphides in a comprehensive and critical manner. Although the review covers the period from 1925 to 1975, it is only in the past ten years that researchers have been fully aware of the implications and problems of chemical reactions, notably oxidation and precipitation reactions, on the surface properties of sulphide minerals. These papers are discussed in more detail than the earlier publications. A table containing a list of determinations of iso-electric- points and points-of-zero-charge of mineral sulphides, and the methods employed in obtaining these results, is presented.